Ursolic acid ameliorates cerebral ischemia-reperfusion injury by inhibiting NF-κB/NLRP3-mediated microglia pyroptosis and neuroinflammation - Liu, Junbin; Zhang, Xiaoting; Guo, Jingpei; Zhang, Yun; Fan, Jinming; Liu, Junfeng; Chen, Jiawen; Jiang, Jiawei; Yu, Benshuai; Zhang, Ke; Zhou, Bin (Frontiers in Pharmacology, 2025)
IntroductionNeuroinflammation is a pivotal factor in the pathophysiology process of ischemic stroke. Undue inflammatory responses are the main cause of neuronal death and infarct enlargement after reperfusion, but there is currently no effective clinical treatment method. Pyroptosis plays an important role in post-stroke neuroinflammation. Inhibiting pyroptosis may be a potential method for treating ischemic stroke. Ursolic acid (UA) is a natural antioxidant with an antipyroptotic effect, but the mechanism of UA in cerebral ischemia-reperfusion injury remains unknown.MethodsWe evaluated UA’s neuroprotective effects in a transient middle cerebral artery occlusion (tMCAO) mouse model via oral administration. TTC staining was carried out to measure infarct volume. Neuronal damage was assessed through TUNEL and FJC staining. Open field test and novel object recognition test were conducted to evaluate anxiety-like behavior and hippocampal-related memory. Double-immunofluorescence was conducted to detect pyroptotic microglia. In vitro, BV-2 microglial cells subjected to oxygen-glucose deprivation/reoxygenation (OGD/R) were treated with UA. Cell viability was measured utilizing CCK-8 assay. RT-qPCR was used to measure NLRP3, IL-1β, and IL-18 mRNA levels. ELISA was utilized to measure IL-1β and IL-18 concentration. PMA was used as an agonist in rescue experiment. Immunostaining was used to observe nuclear/cytoplasmic distribution of NF-κB. Western blot was used to evaluate the protein expression of pyroptosis markers.ResultsUA significantly reduced infarct volume, alleviated neuronal damage, and improved cognitive and functional recovery in tMCAO mice. Additionally, UA downregulated the density of NLRP3, Caspase-1, and GSDMD positive microglia and the production of IL-1β and IL-18 in the ischemic penumbra of tMCAO mice. These effects were replicated in OGD/R-challenged BV-2 cells. Mechanistically, UA suppressed NF-κB activation, and PMA treatment reversed its therapeutic benefits in both models.DiscussionOur findings demonstrate that UA attenuates microglial pyroptosis by inhibiting NF-κB signaling, thereby reducing neuroinflammation and ischemic brain injury. This study highlights UA’s potential as a therapeutic agent for ischemic stroke.